Correlation Between Increasing DNA Copy Numbers That Encode Cortisol Biosynthesis Enzymes and Myocardial Infarction Patients - Duaa Mohammed Al-Nafoly, Sarab D. Alshamaa, Afraa Mohammed Alameen, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The dysfunction in the genes that regulate cortisol production may lead to an increase or overproduction of the hormone and thus affect the functioning of the heart, which may lead to Myocardial infarction. Aim: The aim of our study was to find a correlation between increasing the DNA copy numbers that encode cortisol biosynthesis enzymes and Myocardial infarction disease. Methods: Between the first of January 2021 and the first of July 2021, 120 blood samples from the patients with the acute myocardial infarction (AMI)—60 samples as controls and 60 patients—of both sexes who were admitted to the Unit of the Cardiac Surgery at AL- Salam General Teaching Hospital, the Intensive Cardiac Care Unit, and outpatient health centers in Mousul, Nineveh province/Iraq, were taken. The CYP11A, CYP17A, and CYP11B1 genes implicated in cortisol biosynthesis were found in this work using qRT-PCR. Results: The results of this investigation showed a considerable difference between the age groups of AMI patients and healthy control group in means of amplicon copy counts of CYP11A, CYP17A, and CYP11B1 coding genes. The gene coding for the cytochrome CYP17A enzyme was shown to have a significantly higher number of amplicons in all age groups of the patients, but particularly in the second group (46–56 years) in comparison to healthy control group Conclusion: The results of this study demonstrated for the first time that there were significant correlation between three steroid hormone biosynthesis genes and Acute Myocardial Infarction (AMI) disease by utilizing RT-PCR Technique which revealed a significant increase in the amplicon copy numbers of CYP17 ,CYP11A ,CYP11B genes in all patient's age groups compared with healthy control group. Keywords: AMI patients, Cortisol biosynthesis, CYP17A , CYP11A and CYP11B1 genes.